The hero and the crown - McKinley, Robin (New York : Ace Books, 1987)
Aerin, with the guidance of the wizard Luthe and the help of the blue sword, wins the birthright due her as the daughter of the Damarian king and a witchwoman of the mysterious, demon-haunted North.
Newbery Medal, 1985.
Keywords: Fantasy; Newbery Medal